Pathogenic T Cells in Celiac Disease Change Phenotype on Gluten Challenge: Implications for T‐Cell‐Directed Therapies. Issue 21 (8th September 2021) - Christophersen, Asbjørn; Zühlke, Stephanie; Lund, Eivind G.; Snir, Omri; Dahal‐Koirala, Shiva; Risnes, Louise Fremgaard; Jahnsen, Jørgen; Lundin, Knut E. A.; Sollid, Ludvig M.
Abstract: Gluten‐specific CD4 + T cells being drivers of celiac disease (CeD) are obvious targets for immunotherapy. Little is known about how cell markers harnessed for T‐cell‐directed therapy can change with time and upon activation in CeD and other autoimmune conditions. In‐depth characterization of gluten‐specific CD4 + T cells and CeD‐associated (CD38 + and CD103 + ) CD8 + and γδ + T cells in blood of treated CeD patients undergoing a 3 day gluten challenge is reported. The phenotypic profile of gluten‐specific cells changes profoundly with gluten exposure and the cells adopt the profile of gluten‐specific cells in untreated disease (CD147 +, CD70 +, programmed cell death protein 1 (PD‐1) +, inducible T‐cell costimulator (ICOS) +, CD28 +, CD95 +, CD38 +, and CD161 + ), yet with some markers being unique for day 6 cells (C‐X‐C chemokine receptor type 6 (CXCR6), CD132, and CD147) and with integrin α 4 β 7, C‐C motif chemokine receptor 9 (CCR9), and CXCR3 being expressed stably at baseline and day 6. Among gluten‐specific CD4 + T cells, 52% are CXCR5 + at baseline, perhaps indicative of germinal‐center reactions, while on day 6 all are CXCR5 − . Strikingly, the phenotypic profile of gluten‐specific CD4 + T cells on day 6 largely overlaps with that of CeD‐associated (CD38 + and CD103 + ) CD8 + and γδ + T cells. The antigen‐induced shift in phenotype of CD4 + T cells being shared with other disease‐associated T cells is relevant for development of T‐cell‐directed therapies. Abstract : Celiac disease is driven by CD4 + T cells specific to gluten. Gluten exposure induces expression of potential therapeutic target molecules by the cells. Many newly expressed markers are shared with celiac disease‐associated CD8 + and γδ + T cells being activated (CD38 + ) and gut‐homing (CD103 + ). The findings are relevant to T‐cell‐directed therapy of celiac disease and other T‐cell driven autoimmune conditions.